2021
DOI: 10.3389/fpls.2021.682305
|View full text |Cite
|
Sign up to set email alerts
|

Identification and QTL Analysis of Flavonoids and Carotenoids in Tetraploid Roses Based on an Ultra-High-Density Genetic Map

Abstract: Roses are highly valuable within the flower industry. The metabolites of anthocyanins, flavonols, and carotenoids in rose petals are not only responsible for the various visible petal colors but also important bioactive compounds that are important for human health. In this study, we performed a QTL analysis on pigment contents to locate major loci that determine the flower color traits. An F1 population of tetraploid roses segregating for flower color was used to construct an ultra-high-density genetic linkag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…The linkage maps developed with our two mapping populations presented in this study are on par with the other published high-density SNP-based linkage maps (Bourke et al, 2017b;Zurn et al, 2018Zurn et al, , 2020Cheng et al, 2021;Yu et al, 2021), bringing the total number of tetraploid rose linkage maps reported to seven. The total lengths of our maps were similar to the K5 cut rose mapping population (568.67 cM) (Bourke et al, 2017b), as we also used the default Haldane mapping function and the polymapR implementation of MDSmap (Preedy and Hackett, 2016).…”
Section: Discussionmentioning
confidence: 79%
See 4 more Smart Citations
“…The linkage maps developed with our two mapping populations presented in this study are on par with the other published high-density SNP-based linkage maps (Bourke et al, 2017b;Zurn et al, 2018Zurn et al, , 2020Cheng et al, 2021;Yu et al, 2021), bringing the total number of tetraploid rose linkage maps reported to seven. The total lengths of our maps were similar to the K5 cut rose mapping population (568.67 cM) (Bourke et al, 2017b), as we also used the default Haldane mapping function and the polymapR implementation of MDSmap (Preedy and Hackett, 2016).…”
Section: Discussionmentioning
confidence: 79%
“…Our maps were roughly 100 cM longer than the two garden rose mapping populations (421.92 and 405.42 cM) ( Zurn et al, 2018 , 2020 ) using the Kosambi mapping function. The linkage maps constructed with the Chinese tetraploid YS mapping population using whole-genome sequencing ( Cheng et al, 2021 ) (1285.11 cM) and specific locus amplified fragment sequencing (SLAF-seq) ( Yu et al, 2021 ) (1158.90 cM) were more than double the length of our maps. All the maps described above were constructed using R-package polymapR.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations